A Study of Expiration-day Effects of Index Derivatives Trading in India. Issue 1 (June 2016) - Mahalwala, Rachna
This study examines the existence of expiration-day effects of index derivatives trading in India through volume, return, volatility, and price reversal characteristics of underlying stock market during expiration days of these contracts. Expiration-day effects can be a result of a mixture of factors, including the presence of arbitrage opportunities, the cash settlement nature of index derivative contracts, the stock market process for accommodating the unwinding of arbitrage positions in the stocks, and the efforts to wittingly manipulate prices. Using daily price and turnover data of CNX Nifty and employing time series "ARMA model with EGARCH errors, " the results of the study indicated the presence of some significant but non-disastrous expiration-day effects in India.